Partial regularity of traces of solutions of higher-order nonlinear elliptic systems - Kalita, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For traces of generalized solutions of elliptic systems on smooth manifolds, we study the dependence of the Hausdorff dimension of the set of points at which a solution is not smooth on the modulus of ellipticity of a system.